Pediatric Multisystemic Inflammatory Syndrome (MIS-P) temporarily associated with COVID-19: a survey of clinical and epidemiological characteristics (Research, Society and Development, 2021)
The aim of the present study was to analyze the current scientific literature regarding Pediatric Multisystemic Inflammatory Syndrome (SIM-P) temporarily associated with COVID-19, in order to document the main findings and their therapeutic management. A systematic review of studies was carried out in the databases US National Library of Medicine (PubMed), Scientific Electronic Library Online (Scielo) and ScienceDirect, from September 2020 to February 2021, using the descriptors multisystem inflammatory syndrome, children and COVID-19. The included articles presented observational studies with patients diagnosed with SIM-P, original articles and meta-analyzes published between the years 2020 and 2021. Studies that did not sufficiently describe the data, which were not related to the objective of this review, as well as news, comments, cover letters and duplicates of articles were excluded. Of the 668 studies found, 27 comprised this review. SIM-P affects children and adolescents between 0 and 19 years old, with persistent fever, gastrointestinal symptoms, shortness of breath, abdominal pain and organ dysfunctions. This syndrome is a delayed inflammatory immune response to recent SARS-CoV-2 infection, showing changes in inflammatory markers and other indicators, associated with changes in imaging tests. Therapeutic management aims to reduce the systemic inflammatory response and reestablish organic functions using immunoglobulin, corticosteroids, vasoactive drugs, immunomodulators and anticoagulants. Little scientific evidence is available to understand this syndrome. Thus, multicenter and prospective studies are necessary to better understand the pathophysiology, diagnostic criteria, treatment and existence of medium to long term complications.